Teaching the English article system: Definiteness and specificity in linguistically-informed instruction. (March 2019) - Lopez, Elaine
Many explanations have been offered for the widely attested problems second language (L2) learners experience with the English article system. One influential proposal from formal linguistics is the Article Choice Parameter and associated Fluctuation Hypothesis, which states that learners of English fluctuate between correct and incorrect usage by sometimes selecting articles on the basis of definiteness (correct for English) and sometimes on the basis of specificity (correct for Samoan). The current study trialled new instruction materials which taught specificity then measured the outcome with low-intermediate first language Chinese learners of English ( n = 50). Results show that learners who were taught about specificity did not perform significantly better than learners who were taught about definiteness (using standard teaching materials) or learners who received no instruction on the English article system. The low proficiency of the learners and short intervention period likely contributed to their difficulty understanding the complexities of article meaning. Issues also arose when developing instructional materials which were both linguistically-accurate and sufficiently simple for learners of this level.